Studies on Attributes of Hair and Production Potential of Camel Reared in Semi-intensive Management System - Bhakat, Champak; Mehta, S C; Sahani, M S (Annals of Arid Zone, 2016)
Annual hair yield data from 1038 Indian dromedary camels of 3 breeds (Bikaneri, Jaisalmeri and Kachchhi) from 5 different age groups were recorded. The Bikaneri breed of camel produced significantly (P<O.OI) higher annual hair yields than Jaisalmeri and Kachchhi breed camels and young camels had significantly (P<O.O1) higher yields. The male camel produced significantly (P<O.OI) heavier annual hair clip than females in all breeds and at all age groups. The longest staple length was found in Bikaneri breed followed by Jaisalmeri and Kachchhi breed. The breed and body site significantly (P<O.OI) influenced the staple length. The mean hair diameter of Bikaneri breed was minimum followed by Jaisalmeri and Kachchhi. The hair of male camel was finer than that of female camel. The breed, sex and body site significantly (P<O.OI) affected the hair diameter. The hair diameter in all types of hairs obtained from various sites was finest from Bikaneri breed camels followed by Jaisalmeri and Kachchhi camels. It can be concluded that Bikaneri breed is superior in hair quality attributes as compared to Jaisalmeri and Kachchhi breed and male camel of Bikaneri breed belonging to 3-year-age groups produced higher annual hair yield as compared to camels of other breed, age and sex. Key words: Camel, hair attributes, management system, rearing. Â